ANALISA INTENSITAS HUJAN DI SUNGAI SUNTER JAKARTA UTARA - Schulz, Niki Gustav; Nisa, Mitsaq Addina (Jurnal Kajian Teknik Sipil, 2021)
AbstractThe amount of rainfall intensity in an area is very important to be known, studied, discussed and studied in civil engineering. Analysis of rainfall intensity in a watershed can be calculated by several methods, for daily rainfall data the intensity can be calculated using the Mononobe method. This study aims to calculate the intensity of rainfall in the Sunter River using the Mononobe method. Rain data in this study uses daily rain data from the Tj. North Jakarta Priok. The calculation of the data in this study was carried out with the help of Microsoft Excel program. The results of this study indicate that the Mononobe method is able to calculate the amount of rain intensity in the Sunter River based only on daily rainfall data. Keywords: Rainfall Intensity, Sunter River, Mononobe Methode